Diurnal and nocturnal activity patterns and habitat use of Algoa Bay's rocky reef fish community - Juby, Roxanne (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2017)
Distinct day-night changes in ambient light are recognised as an important driver of animal activity patterns, with predictable changes to the structure and composition of animal communities between day and night. While day-night variation in the structure of animal communities has been well researched for terrestrial organisms and shallow marine fish communities around the world, there has been limited research of this type conducted on South Africa's rocky reef fish communities. Consequently, we have a poor understanding of how nocturnal reef fish communities are structured and the day-night activity patterns of species inhabiting both shallow (10-30m) and deep-aphotic (55-100m) reefs. This research was conducted at two warm-temperate South African rocky reefs situated in Algoa Bay. The importance of natural ambient light in shaping the distribution of reef fish communities at shallow and deep-aphotic reef sites was demonstrated using baited remote underwater stereo-video systems (stereo-BRUVs). Distinct day and night fish communities were sampled at shallow and deep-aphotic reef sites. These differences were driven by significant changes in species richness (p < 0.001), species abundance (p < 0.001) and community composition (p < 0.001). These shifts appeared to be driven by day-night activity patterns that were the result of increased detectability of certain species at either day or night. The majority of species belonging to the family Sparidae showed evidence of strict diurnal activity, with their activity being further restricted to shallow reefs. These species showed evidence that they may enter micro-habitats within the reef at night. Similar activity patterns were shown for other top predatory teleost species and low level consumers, with substantial reductions in abundances, or no recordings at night throughout this study. Shallow reefs at day harboured the most diverse fish community. It is therefore hypothesised that this habitat was associated with conditions that offered improved access to resources for many visual species. In addition, the diverse community inhabiting shallow reefs at day is associated with a high risk of negative interspecies interactions, such as competition and predation. It is hypothesised that the biotic conditions associated with shallow reefs at day drove three movement patterns identified in this study; Pagellus bellottii natalensis showed evidence of movement onto shallow reefs at night from adjacent sandy flats, while Pterogymnus laniarius and Squalus sp. 1 showed evidence of movement onto shallow reefs at night from the deep- aphotic reefs that remain dark throughout the diel cycle. It is further hypothesised that other species which showed evidence for nocturnal activity, i.e. Galeichthys ater, Eptatretus hexatrema and Haploblepharus edwardsii, may enter sheltered micro-habitats within the reef during day light hours. These findings have highlighted the complex patterns that have evolved within marine fish to allow multiple species to coexist and exploit productive reef ecosystems by partitioning resource use and activity patterns at day or night, between depth zones and habitat types.
Keywords: Reef fishes -- Effect of light on; Reef fishes -- South Africa; Underwater videography in wildlife monitoring -- South Africa -- Tsitsikamma